Structural and functional impact of missense mutations in TPMT: An integrated computational approach. (December 2015) - Fazel-Najafabadi, Esmat; Vahdat Ahar, Elham; Fattahpour, Shirin; Sedghi, Maryam
Graphical abstract: Highlights: Pathogenecity of TPMT mutations could be predicted by an integrative approach. Most of the mutations resulting in no enzyme activity are in conserved positions. Missense mutations have different effects on TPMT structure and function. Residue interaction network of approximately 85% of the alleles are different from wild type. Cytoscape is a robust program for visualization of residue interaction network in TPMT. Abstract: Background: Thiopurine S-methyltransferase (TPMT) detoxifies thiopurine drugs which are used for treatment of various diseases including inflammatory bowel disease (IBD), and hematological malignancies. Individual variation in TPMT activity results from mutations in TPMT gene. In this study, the effects of all the known missense mutations in TPMT enzyme were studied at the sequence and structural level Methods: A broad set of bioinformatic tools was used to assess all the known missense mutations affecting enzyme activity. The effects of these mutations on protein stability, aggregation propensity, and residue interaction network were analyzed. Results: Our results indicate that the missense mutations have diverse effects on TPMT structure and function. Stability and aggregation propensities are affected by various mutations. Several mutations also affect residues in ligand binding site. Conclusions: In vitro study of missense mutation is laborious and time-consuming. However, computational methods can be used to obtain information about effects of missense mutations on protein structure. In this study, the effects of most of the mutations on enzyme activity could be explained by computational methods. Thus, the present approach can be used for understanding the protein structure-function relationships.